Influencing factors and risk prediction modeling of maternal postpartum depression: a cross-sectional study in Chinese puerperal women of sitting the month - Su, Xiaojuan; Zhang, Yuezhen; Chen, Meide; Wang, Huifang; Liu, Guihua (Frontiers in Psychiatry, 2023)
Objective This study aims to investigate the occurrence of maternal postpartum depression (PPD) during menstruation and analyze the influencing factors and risk prediction modeling of maternal PPD in Chinese puerperal women of sitting the month. Methods A total of 286 mothers were selected using convenience sampling, who came for a routine postpartum follow-up visit were surveyed, including face-to-face, telephone, and online. They completed questionnaires including the basic profile questionnaire, Postpartum Partner Support Scale (PPSS), Edinburgh PPD Scale (EPDS), Parenting Self-Efficacy Scale (SICS), and Simple Coping Style Questionnaire (SCSQ), who were advised to complete the survey alone, in private, reducing the impact of husband’s presence on the quality of the questionnaire. Variables showing statistical significance in the one-way analysis were further analyzed using logistic regression analysis. The predictive value of the logistic regression model was analyzed using the Receiver Operating Characteristic Curve (ROC), and the predictive reliability was expressed as the area under the ROC [Area Under the Curve (AUC)]. Results The total score of PPD was 7.78 ± 4.57, and 22 people (7.69%) experienced depression during the postpartum period. PPD was found to be correlated with postpartum partner support, positive coping, negative coping, and parenting self-efficacy, with correlation coefficient values of −0.63, 0.62, 0.56, and − 0.70, respectively (all p < 0.05). Logistic regression analysis revealed that postpartum partner support and parenting self-efficacy were independent factors influencing PPD, with odds ratios (95% confidence intervals) of 0.76 (0.61 0.94) and 0.83 (0.75 0.93), respectively both p < 0.05.The area under the curve, sensitivity, and specificity for postpartum partner support and parenting self-efficacy were 1.00 (95% confidence intervals 0.99 1.00), 99.24, and 90.91%. Conclusion Postpartum partner support and parenting self-efficacy independently predict the occurrence of PPD. Healthcare professionals and maternal families should prioritize timely attention to maternal partner support and parenting issues to reduce the occurrence of PPD.